1999
DOI: 10.1177/01939459922044045
|View full text |Cite
|
Sign up to set email alerts
|

Male Caregivers’ Use of Formal Support

Abstract: The purpose of this study was to explore male caregivers' perceptions of formal support. The men were caregivers of adults with cognitive impairment. The study involved secondary analysis of interview data on perceptions of support that had not been previously analyzed from the perspective of formal support. Techniques of data analysis used in grounded theory were applied to 62 guided interactive interviews conducted with 24 male caregivers during a period of 18 months. The men experienced a process of making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 63 publications
7
68
1
7
Order By: Relevance
“…Both groups underutilized formal community services, supporting previous research that showed low levels or inappropriate levels of formal services (Brodaty et al, 2005;Coe & Neufeld, 1999;Cossette et al, 1995;Gwyther, 1994;Kadushin, 2004). Wives, more than husbands, had difficulty recognizing problems in the spouse and therefore delayed seeking a diagnosis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Both groups underutilized formal community services, supporting previous research that showed low levels or inappropriate levels of formal services (Brodaty et al, 2005;Coe & Neufeld, 1999;Cossette et al, 1995;Gwyther, 1994;Kadushin, 2004). Wives, more than husbands, had difficulty recognizing problems in the spouse and therefore delayed seeking a diagnosis.…”
Section: Discussionsupporting
confidence: 71%
“…Some studies have suggested that male caregivers use services more often (Coe & Neufeld, 1999;Laditka, Pappas-Rogich, & Laditka, 2001). However, Cossette and colleagues (1995) found that underutilization was consistent across genders in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Zarit et al 1986;Lüdecke et al's 2012), there is also research on caregiving men which has shown that norms of gender may get in the way of caregiving men's willingness to use formal support because caregiving and masculinity are not synonymous (e.g. Coe and Neufeld 1999;Lin et al 2012;Sanders 2007).…”
Section: Caregiving Men In Previous Researchmentioning
confidence: 99%
“…Male caregivers resisted formal help, and preferred to handle their allocated tasks by themselves. 22 Women seemed to be more prone to relational deprivation, which is a restriction in one's social life and feelings of social isolation. 3,23 It has been noted that women tend to use more emotion-focused coping strategies whilst men utilise more problem-focused methods.…”
Section: Introductionmentioning
confidence: 99%